ПАРАМЕТРИ ХОЛЛОВСЬКОГО ДВИГУНА ST-40M ПРИ РОБОТІ НА КСЕНОНІ І КРИПТОНІ - ASMOLOVSKYI, S. YU.; VORONOVSKYI, D. K.; KULAHIN, S. M.; MASLOV, V. V.; PERERVA, V. O.; TROIAN, A. O.; YURKOV, B. V. (текст 3, 2025)
DOI: https://doi.org/10.15407/itm2025.04.043 This article presents the results of an experimental study of the parameters of the ST-40M Hall-effect thruster developed by SETS (Space Electric Propulsion Systems) in its operation on xenon and krypton. Electric propulsion systems based on Hall-effect thrusters have found wide application due to their high performance and relative simplicity of design and operation compared to other types of propulsion systems. Traditionally, xenon is used as propellant in Hall-effect thrusters. It is an inert gas with a low ionization energy and a high atomic mass, which makes it possible to achieve a high performance of the electric propulsion system while maintaining operational simplicity. However, the high cost of xenon significantly affects the overall expenses during the testing and operation of the thruster and the propulsion system. Therefore, research is underway on the use of alternative propellants that could reduce operating costs while maintaining the thruster performance at an acceptable level. The most promising alternative to xenon is considered to be krypton. It has a lower cost and ensures operational simplicity, but its higher ionization energy negatively affects the thruster efficiency. The goal of this work was to compare the main parameters of the thruster operating on xenon and krypton under identical conditions. Experimental tests were carried out in a vacuum chamber at discharge voltages ranging from 250 to 500 V and propellant mass flow rates from 1 to 1.78 mg/s for xenon and from 1 to 1.6 mg/s for krypton. A comparative analysis of the thruster parameters in its operation on xenon and krypton at a mass flow rate of 1 mg/s showed that the use of krypton leads to a deterioration in thruster performance. The anode thrust and specific impulse decreased by 25 %–37 %, while the anode efficiency dropped by 15 %–24 %. REFERENCES 1. Frongello B., Hoskins W., Cassagy R., Kalkowska L., Maliga R. Spacecraft electric propulsion at an inflection point. Proceedings of the ASCEND Conference, AIAA paper 2021-4151, 2021.https://doi.org/10.2514/6.2021-4151 2. Tirila V. G., Demairé A., Ryan C. N. Review of alternative propellants in Hall thrusters. Acta Astronautica. 2023. V. 212, Pp. 284-306. https://doi.org/10.1016/j.actaastro.2023.07.047 3. Asmolovskyi, S., Yurkov, B. Analysis of the effect of changing the working substance from xenon to alternative inert gases on the parameters of the Hall-type electric propulsion system. System Design and Analysis of Aerospace Technique Characteristics. 2023. V. 33. No. 2. Pp. 3-22. (In Ukrainian). https://doi.org/10.15421/472308 4. Thomas F., Munro-O'Brien, Ryan C. N. Effect of channel width on the performance of a modular Hall effect thruster operating on Xenon, Krypton, and Argon. 39th International Electric Propulsion Conference 2025, IEPC-2025-193. 5. Thoreau P., Little J. M., Johansen A., Holmes M. R. Modeling and optimization of propellant mixtures for Hall thrusters. 39th International Electric Propulsion Conference 2025, IEPC-2025-071. 6. Moghaddasi M. B., Byrne M., Glascock M., Foster A. Qualification of ExoTerra's Halo8 Hall-effect thruster on krypton propellant. 39th International Electric Propulsion Conference 2025, IEPC-2025-441. 7. Kitaeva A., Di Sarli A., Giusti N., Pisano V., Pieri L., Cecconi M., Binetti C., Torre L., Gregucci S., Cardelli M., Ciampini D. SITAEL HT5k and HT20k propulsion systems readiness. 38th International Electric Propulsion Conference 2024, IEPC-2024-726. 8. Petrenko, O., Troyan, A., Pererva, V. Parameters of the ST-40M Hall thruster with increased power discharge supply. Journal of Rocket-Space Technology. 2023. V. 31. No. 4. Pp. 50-58.https://doi.org/10.15421/452307 9. Tolok S., Shcherbak D., Petrenko O., Troian A., Yurkov B. LAB6 hollow cathode with wide range current operation. У 73rd International Astronautical Congress, 2022. 10. Voronovskyi D., Kulahin S., Yurkov B., Asmolovskyi S. Performance comparison of a traditional and a magnetically shielded Hall thruster. Teh. Meh. 2025. No. 2. Pp. 50-62. (in Ukrainian).https://doi.org/10.15407/itm2025.02.050 11. Glascock M. S., Kiefer E., VanWoerkom M. Performance and capability overview of the Halo electric propulsion system. 37th International Electric Propulsion Conference 2022, IEPC-2022-301. 12. Jakubczak M., Riazantsev A., Jardin A., Kurzyna J. Experimental optimization of small krypton Hall thruster for operation at high voltage. 37th International Electric Propulsion Conference 2022, IEPC-2022-360. 13. Xia G., Li H., Ding Y., Wei L., Chen S., Yu D. Performance optimization of a krypton Hall thruster with a rotating propellant supply. Acta Astronautica, 2020 V. 171. Pp. 290-299.https://doi.org/10.1016/j.actaastro.2020.03.021